Extremely Vibrant Routing Scheme for Mobile Adhoc Network - Syes Abdul Syed S; T Senthil Kumaran (Institute of Advanced Engineering and Science, 2018)
This paper aims to improve the performance of the traditional routing protocol for MANET such as DSR and AODV in terms of delay and overhead. The proposed routing scheme is called as Extremely Vibrant Routing (EVR) which adopts with the highly dynamic environment of MANET. The link residual life is estimated to reduce the link failure before forwarding data through a node. The velocity of the moving mode is considered while choosing the next forwarder node. This enables the EVR to decrease the delay in the network. The proposed routing scheme reduces routing overhead and reduces the delay. This scheme reduces the link failure too. The performance is evaluated by using the simulation results obtained by using NS2 simulator.